The Influence of Situational Leadership and Orgnazational Culture on Educator Performance at State Madrasah Aliyah Post Covid 19 Pandemic - fetrimen, fetrimen; Hellena, Rosyaida Saara (Universitas Islam Negeri Raden Intan Lampung, 2023)
Educator performance was one of success factor on quality education system. The educator performance was depend on the situational leadership of Headmaster and organizational culture. This research aims was to analyze performance of educators Madrasah Aliyah Negeri (MAN) after the Covid-19 pandemic which was influenced by the leadership of situational of madrasah head and organizational culture in East Jakarta. This research used quantitative approach to path analysis, techniques collection data were implementation using the survey method by distributing questionnaires via google forms to 150 educators State Madrasah Aliyah (MAN) at East Jakarta. This research was conducted for 3 months. The results of this research found a significant effect about performance of educators influenced by the leadership of situational of the headmaster and organizational culture.